Accurate peak fitting and subsequent quantitative composition analysis of the spectrum of Co 2p obtained with Al Kα radiation: I: cobalt spinel. (6th January 2016) - Cabrera‐German, Dagoberto; Gomez‐Sosa, Gustavo; Herrera‐Gomez, Alberto
Abstract : Employing state‐of‐the‐art and practical peak‐fitting and background modeling methods (active approach), we obtained high quality fitting of the photoemission spectrum of Co 2 p in cobalt spinel. The concurrent analysis of both 2 p 3/2 and 2 p 1/2 branches played a fundamental role. It revealed various Auger features that interfere with the main photoemission lines. It was possible to accurately reproduce the corresponding composition (Co3 O4.0 ± 0.25 ) and to report the relative intensity of the various multiplet/satellite peaks including the associated uncertainties. Copyright © 2016 John Wiley & Sons, Ltd.